When Harpagon Sleeps in the Bath. Performances of the Works of Molière at PIF - Kroflin, Livija (Molière u hrvatskoj kulturi, 2024)
Characters from comedies are not psychologically well-developed characters, but stereotypes with fixed characteristics. They often represent the incarnation of a single characteristic, that is, a fault, meaning that the audience experiences them as extremely simplified and not very realistic, and they are a major challenge for actors. Puppet theatre, on the other hand, is a theatre of symbols and metaphors. It has no need for fine, psychological characterisation, it gladly deals with stereotypes, and as a result it is actually ideal for performing farces and comedies. Although Croatian puppet theatres were not interested in staging Molière’s comedies, the Croatian public had the opportunity to see some of them at PIF (the International Puppet Theatre Festival in Zagreb). There were visiting productions of Molière (first performed in 1998) by the Stuffed Puppet Theatre from The Netherlands, Don Juan (1995) by the KONJ puppet theatre from Slovenia, The Imaginary Invalid (1998), a production which the Croatian artist Zlatko Bourek staged at the Puppet Theatre in Ljubljana, and The Miser (2003) produced by the Tàbola Rassa puppet company from Spain. This last was particularly interesting in terms of its puppets, because Harpagon was depicted as collecting water instead of gold as the greatest treasure. As a result he slept in a bath to prevent any kind of misuse, and when he made his own daughter weep because of his stubbornness, he rushed to collect all her tears so that not a drop of the valuable liquid would be lost. This meant that the puppets representing the characters in the production were made from various forms of taps, with the addition of only a piece of cloth. Apparently simple, but theatrically very effective and completely justified by the text.